(untitled) (Research, Society and Development, 2022)
Objective: To understand the prevalence of excessive use of entertainment technologies in the daily lives of children and adolescents with psychiatric vulnerability, so that we can better deal with these innovations within the health area. Method: This work is a descriptive, quantitative and prospective cohort study, with data collection via a questionnaire made available to patients at CAPS-I in Cascavel. Result: There was no correlation between the exacerbated use of technologies and the most prevalent psychiatric disorders, nor an association with sleep, sex, age, treatment time in CAPS-I and electronic devices most used by patients, however, a statistically relevant relationship between the use of these tools and the amount of weekly social interactions in groups. Conclusion: The use of technologies proved to be a favorable factor for face-to-face social interactions, however its relation with the other factors surveyed was not proven.